Methods and methodologies in Fiqh and Islamic economics - Saleem, Muhammad Yusuf (International Association for Islamic Economics, 2010)
This paper discusses the methodology and methods of reasoning in fiqh and critically examines their application to Islamic economics. It argues that fiqh methods are mainly designed to find out whether a certain act is permissible or prohibited for an individual. Islamic economics, on the other hand, is a social science and, accordingly, its proper unit of analysis is society, not the individual. Methodologies of fiqh and Islamic economics also differ as the former focuses on prescriptions. It prescribes what an individual should do or avoid. In contrast, Islamic economics is more concerned with describing economic realities. While fiqh prescriptions are permanent in nature and for all individuals, economic descriptions may change from time to time and from society to society. This paper argues that the methods of reasoning in fiqh and Islamic economics are not necessarily the same. While fiqh is well served by its methodology and methods set out in usul al-fiqh, Islamic economics should rely on a methodology and methods that suit its social and descriptive nature.